The Influence of Leadership Style and Work Motivation on Teacher Performance (Study on Teachers of SMPN 18 Bandung City) - Siti Hafsoh; Deden Komar Priatna; R Jusdijachlan (Greenation Research & Yayasan Global Resarch National, 2023)
The purpose of this study was to determine and analyze: (1) Leadership Style; (2) Work Motivation; (3) Teacher Performance; and (4) the influence of leadership style and work motivation on teacher performance at SMP Negeri 18 Bandung, both simultaneously and partially. This study uses a quantitative approach with multiple regression analysis. The source of research data is primary data. The unit of analysis in this study was the teachers of SMP Negeri 18 Bandung. The research data was collected using a questionnaire via google form with a population of 46 respondents using the census method where all members of the population were involved in this study. The results showed that the leadership style was included in the good category, work motivation was in the doubtful/good enough category and teacher performance was in the very good category. Leadership Style and Work Motivation simultaneously have an effect on the performance of SMP Negeri 18 Bandung teachers. However, partially leadership style is more dominant in influencing teacher performance compared to work motivation. Thus the main priority is to maintain a leadership style that has been going well so that the teachers of SMP Negeri 18 Bandung can work effectively in carrying out their duties.